The use of sodium alginate-based coating and cellulose acetate in papaya post-harvest preservation - Silva, Denise Andrade; Oliveira, Juliana Krieger; Santos, Clovis Marcelo; Bery, Carla Crislan Souza; Castro, Alessandra Almeida; Santos, João Antônio Belarmino (Acta Scientiarum. Technology, 2014)
This study aimed to evaluate the ripening of papaya fruit (Carica papaya L.) at room temperature (±25°C) and10°C with 80% relative humidity, coated with edible film based on sodium alginate (1%) and cellulose acetate film (3%) by dipping the fruit in the suspensions for 1 min. On the application of the treatment and every three days during 12 days of storage, fruit were evaluated for weight loss, firmness, total carotenoid content, lycopene content and vitamin C content of the pulp. The cellulose acetate film extended the shelf-life of papayas, without affecting their quality. This treatment delayed fruit ripening, whose changes in all the parameters analyzed were significantly slower than fruit treated with sodium alginate-based coating. The coating with cellulose acetate at 3% was more effective in the preservation of papaya stored for 12 days under both temperatures.